UPAYA GURU AQIDAH AKHLAK DALAM PEMBENTUKAN KARAKTER SISWA DI MA MUALLIMIN JAGALAN MALANG - Muhammad Saifulloh; Nur Hasan; Lia Nur Atiqoh Bela Dina (VICRATINA, 2020)
Lack of moral education has become rampant in the world of education,  which has resulted in a generation of poorly educated people, this  can be seen from the rampant drug cases that ensnare students, rampant fight between students, etc         religious educatin teachers must be able to use various forms in shaping the character of students, morals are an important thing that must be owned by every one who has students who are better than those seen from the morals in their possession. Inthis day and age, there are so many phenomena about the decline in character that students like that it is negative for families to avoid thinking in accordance with the theacings of islam in overcoming this need of teacher assistance to create character.